Using Standardized Health Consumer Indicators as a Policy Development Tool - Cătălin Ovidiu BABA; Răzvan M. CHERECHEŞ; Alexandra BRÎNZANIUC; Olimpia MOŞTEANU (Transylvanian Review of Administrative Sciences, 2007)
This study describes the relations between the European Union standardized health indicators and the community-based health policy. One of the goals of the European Commission is to provide standardized information on health in order to make it comparable at a trans-national level. Hence, numerous projects aimed at developing health indicators, and improving databases relating to these were supported by the Program of Community Action in the Field of Public Health. In this paper the authors argue that standardized health indicators can provide more than a prototype for a future health monitoring system. Bearing in mind that the production of comparable information on health is based upon four different tasks (the analysis of data needs in a specific area, definition of indicators and quality assurance, reporting and analysis, and promotion of the results) the authors assert that all of these tasks are important steps towards the development of community-based health policy. Thus, the main objective of this study is to analyze their utility as premises for policy development.